e-VITA study protocol: EU-Japan virtual coach for smart aging - Bevilacqua, Roberta; Stara, Vera; Amabili, Giulio; Margaritini, Arianna; Benadduci, Marco; Barbarossa, Federico; Maranesi, Elvira; Rigaud, Anne-Sophie; Dacunha, Sébastien; Palmier, Cecilia; Moller, Johanna; Browne, Ryan; et al. (Frontiers in Public Health, 2024)
Aim: To report a trial protocol for assessing the improvement of older people's well-being, promoting active and healthy ageing and reducing the risks of social exclusion, using a virtual coach. Background: Increased longevity brings with it reduced autonomy and independence, and it is therefore necessary to act with preventive measures that can promote active and healthy ageing. With the development of technology, new tools have appeared, including virtual coaches, which can enable people to lead a healthy lifestyle by identifying individual needs and goals and providing personalized recommendations and advice. However, it is important that these coaches take into consideration the inter-individual and cross-cultural differences of each person. Design: Randomized controlled trial is proposed. Methods: This study will recruit 240 healthy subjects aged 65 years and older and are recruited. Participants will be assigned to an experimental group that will receive the e-VITA system or to the control group that will receive an information booklet only. The primary outcome measure is the person's quality of life (QoL). Data will be collected at baseline, three months after the trial, and at the end of the trial, after six months. Discussion: This study will evaluate the effectiveness of the e-VITA system, consisting of a virtual coach, several sensors for monitoring, a smartphone for use at home, and a booklet, in improving the older person's quality of life. The increased perceived well-being will also be linked to improvements in other areas of the person's life, psychological and cognitive status, the area of sociality, nutrition, and eHealth literacy.